Peer mentoring in medical residency education: A systematic review - Pethrick, Helen; Nowell, Lorelli; Oddone Paolucci , Elizabeth; Lorenzetti, Liza; Jacobsen, Michele; Clancy, Tracey; Lorenzetti, Diane (Canadian Medical Education Journal, 2020)
Background: Medical residents may experience burnout during their training, and a lack of social support. This can impact their overall wellbeing and ability to master key professional competencies. We explored, in this study, the extent to which peer mentorship promotes psychosocial wellbeing and the development of professional competencies in medical residency education. Methods: We searched six databases (MEDLINE, EMBASE, PsycINFO, Academic Research Complete, ERIC, Education Research Complete) for studies on peer mentoring relationships in medical residency. We selected any study where authors reported on outcomes associated with peer mentoring relationships among medical residents. We applied no date, language, or study design limits to this review. Results: We included nine studies in this systematic review. We found that medical residents received essential psychosocial supports from peers, and motivation to develop academic and career competencies. Medical residents in peer-mentoring relationships also reported increased overall satisfaction with their residency training programs. Conclusions: Peer-mentoring relationships can enhance the development of key professional competencies and coping mechanisms in medical residency education. Further rigorous research is needed to examine the comparative benefits of informal and formal peer mentoring, and identify best practices with respect to effective design of peer-mentorship programs.